Synthesis and Properties of C2h-Symmetric BN-Heteroacenes Tailored through Aromatic Central Cores - Wang, Xinyang; Zhang, Fan; Gao, Jianhua; Fu, Yubin; Zhao, Wuxue; Tang, Ruizhi; Zhang, Wanzheng; Zhuang, Xiaodong; Feng, Xinliang (Journal of Organic Chemistry, 2015)
The 2-fold successive electrophilic borylation on one aromatic central core led to a series of C2h-symmetric BN-heteroacenes in excellent yields. For the first time, we introduced trimethylsilyl (TMS) as either leaving group or oriented group for efficiently improving the preparation of BN-embedded polycyclic aromatic hydrocarbons (PAHs). The physical properties of the as-synthesized BN-heteroacenes in either solid state or solution can be finely tuned through the position isomerization or the fused ring numbers of the aromatic central core.
CRIS-Team Scopus Importer:2023-03-20